"Breast in a Day": Examining Single-Stage Immediate, Permanent Implant Reconstruction in Nipple-Sparing Mastectomy. Issue 2 (August 2016) - Choi, Mihye; Frey, Jordan D.; Alperovich, Michael; Levine, Jamie P.; Karp, Nolan S.
Abstract : Background: Nipple-sparing mastectomy with immediate, permanent implant reconstruction offers patients a prosthetic "breast in a day" compared to tissue expander techniques requiring multiple procedures. Methods: Patients undergoing nipple-sparing mastectomy with immediate, permanent implant reconstruction were reviewed with patient demographics and outcomes analyzed. Results: Of 842 nipple-sparing mastectomies from 2006 to June of 2015, 160 (19.0 percent) underwent immediate, permanent implant reconstruction. The average age and body mass index were 46.5 years and 23.3 kg/m 2 . The majority of implants were either Allergan Style 20 (48.1 percent) or Style 15 (22.5 percent). The average implant size was 376.2 ml, and 91.3 percent of reconstructions used acellular dermal matrix. The average number of reconstructive operations was 1.3. Follow-up was 21.9 months. The most common major complication was major mastectomy flap necrosis (8.1 percent). The rate of reconstructive failure was 5.6 percent and implant loss was 4.4 percent. The most common minor complication was minor mastectomy flap necrosis (14.4 percent). The rates of full-thickness and partial-thickness nipple necrosis were 4.4 and 7.5 percent, respectively. Age older than 50 years ( p = 0.0276) and implant size greater than 400 ml ( p = 0.0467) emerged as independent predictors of overall complications. Obesity ( p = 0.4073), tobacco use ( p = 0.2749), prior radiation therapy ( p = 0.4613), and acellular dermal matrix ( p = 0.5305) were not associated with greater complication rates. Conclusion: Immediate, permanent implant reconstruction in nipple-sparing mastectomy provides patients with a breast in a day in less than two procedures, with a low complication rate. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.